Perancangan sistem informasi akuntansi penjualan kain pada CV Vidi Sukses Berkah menggunakan microsoft visual basic 2010 - Refiani S, Refa; Hamdani, Masayu; Muthmainnah, Muthmainnah; Syahidin, Yuda (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of the research is to design a sales accounting information system in CV Vidi Sukses Berkah. The method of collecting data is through observation, interviews and literature studies relating to the subject matter of the research conducted. The problem found is that the sales system still uses a manual system where sales transaction data is still handwritten in the form of notes on notes, resulting in frequent damage to data such as torn or dirty notes. Therefore, a desktop-based sales information system was designed using the waterfall model system development method and tools such as Flowmap, DFD and ERD. Based on the results of research conducted by the author, it can be concluded that with a sales information system the company can streamline the process of managing fabric sales transactions, improving customer service and controlling sales transactions directly because of automatic reports presented by the system with daily periods.